Participation of Italian Communists in Catholic Rituals: A Case Study - Kertzer, David I. (Journal for the scientific study of religion, 1975)
The nature of participation of Italian Communists in the ritual of the Catholic Church is examined. Two models are presented--a normative marxist model excluding Church participation by Communists and a popular Italian model which portrays the mass of Communists as being fundamentally Catholic. Neither model is found to be satisfactory in light of the evidence from the locality under study. It is found that the great majority of the Communists continue to turn to the Church for rites of passage. At the same time, however, the Communist Party has to a great extent supplanted the local churches as the sponsor of "rites of community."